Developing the educational performance of learning disabilities teachers in primary schools: ChatGPT program as a model - Hegazy, Ahmed Zakaria (International Journal of Innovative Research and Scientific Studies, 2025)
To explore primary school teachers’ views on integrating ChatGPT into education in Al-Ahsa, Saudi Arabia, concentrating on awareness, usage, and challenges. The study applied mixed methods, involving a survey conducted with 434 teachers through stratified sampling and in-depth interviews, whereby data were analyzed to assess teachers’ awareness, implementation practices, and perceived challenges. In-depth interviews were conducted with 87 teachers who had prior experience using ChatGPT to gain further insights into their experiences. Few teachers (20%) were aware of ChatGPT, confirming low levels of awareness and use in classroom situations. Teachers who were aware of ChatGPT cited its advantages in promoting better teaching methods and engaging students; however, the views on the effectiveness of ChatGPT for teaching scientific subjects were moderate. Challenges cited include technical difficulties, curriculum alignment, and adjusting instruction for different learning styles. The findings reflect the need for more teacher training and professional development that enhances the integration of ChatGPT into the educational sphere. Once these gaps are addressed, ChatGPT can be better utilized to its full potential with fair access. Educators, policymakers, and innovators may utilize these thought processes to design specific training courses targeted to their curriculum, thereby facilitating technology adoption. By providing working partnerships, stakeholders may help improve educational outcomes for learning-disabled students as well as advance technology education in primary schools.